Die Welt zur Zeit Jesu - Dahlheim, Werner (Verlag C.H. Beck, 2013)
When Pontius Pilate washed his hands of the matter and Roman soldiers flogged Jesus of Nazareth and dragged him through the streets of Jerusalem to Calvary, no one suspected that the death of this Jewish itinerant preacher would mark a turning point in history. Than a few decades later when the Second Temple went up in flames and Jerusalem was destroyed, the Christians had already left on their first missionary journeys into the world. But what was this world over which the new faith spread? Rome was the all-conquering power that local conflicts--whether religious or political in nature--sometimes fueled, sometimes leaked under the boots of the Legionaries. The word of the governor, the greed of the tax collectors and the glamorous royal household Roman potentates certain life around the Mediterranean. Whether Greek or Egyptian mysteries thinking whether oriental spices or Gallic slaves - all drawn to Rome, and thus increased its luster. Werner Dahlenheim in his book designs a panorama of the world of Jesus' time.